Performance Evaluation Method Biology Learning Project as An Effective Teaching Tool - Shirinzada Nijat, Ulya (International Journal of Humanities and Education Development (IJHED), 2023)
The purpose of this study is to investigate the effect of project-based learning and thinking ability in biology classes. The research analyzed a sample of students from two distinct grades using pre-test and post-test. Following that, the findings revealed that members of the experimental group I, which included students who engaged in project-based, learning, had the best learning outcomes. In a project-based learning environment, students gained knowledge and skills by working collaboratively for an extended period on a real-world question or problem. Students trained using this model had better indicators of thinking ability than students trained using the traditional learning model. Thus, teachers must use the project-based learning model to guarantee better results while also improving students' thinking abilities to increase the model's efficacy. Schools can promote collaboration, agency, and effective communication skills by teaching social studies using project-based learning. PBL also allows students to address real-world issues in their community and around the globe.